Fleur-de-lis Abdominoplasty and Neo-umbilicus - Mendes, Flavio Henrique [UNESP]; Donnabella, Alfredo [UNESP]; Fagotti Moreira, Alan Roberto [UNESP] (Elsevier B.V., 2019)
Body contouring for patients with massive weight loss may demand not only lifting but also some extent of central body tightening to achieve complete tissue readjustment. Although the fleur-de-lis procedure usually achieves nice contouring results, poor visible scars, including umbilical complications, have restricted the indications for the anterior vertical approach. The purpose of this article is to present the authors' experience with the inner scar umbilical reconstruction, enhancing overall results for vertical abdominoplasties. The inner scar umbilicus is a simple, safe, and reproducible technique, presenting low complication rates with sustainable and natural results.
Keywords: Massive weight loss; Body contouring; Neo-umbilicoplasty; Post-bariatric; Vertical abdominoplasty